On-road emission characteristics of VOCs from rural vehicles and their ozone formation potential in Beijing, China. (March 2015) - Yao, Zhiliang; Wu, Bobo; Shen, Xianbao; Cao, Xinyue; Jiang, Xi; Ye, Yu; He, Kebin
Abstract: This paper is the second in a series of papers aimed at understanding volatile organic compound (VOC) emissions from motor vehicles in Beijing using on-board emission measurements, focusing specifically on rural vehicles (RVs). In this work, 13 RVs, including 6 different 3-wheel (3-W) RVs and 7 different 4-wheel (4-W) RVs, were examined using a portable emissions measurement system (PEMS) as the vehicles were driven on predesigned fixed test routes in rural areas of Beijing. Overall, 50 VOC species were quantified in this study, including 18 alkanes, 5 alkenes, 11 aromatics, 13 carbonyls and 3 other compounds. The average emission factor (EF) of the total VOCs for the 4-W RVs based on the distance traveled was 326.2 ± 129.3 mg/km, which is 2.5 times greater than that of the 3-W RVs. However, the VOC emissions for the 3-W RVs had higher EFs based on their CO2 emissions due to the different fuel economies of the two types of RVs. Formaldehyde, toluene, acetaldehyde, m-xylene, p-xylene, isopentane, benzene, ethylbenzene, n-pentane, 2-methoxy-2-methylpropane and butenal were the dominant VOC species from the RVs, accounting for an average of 68.6% of the total VOC emissions. Overall, the RVs had high proportions of aromatics and carbonyls. The ozone formation potentials (OFPs) were 670.6 ± 227.2 and 1454.1 ± 643.0 mg O3 /km for the 3-W and 4-W RVs, respectively, and approximately 60%–70% of the OFP resulted from carbonyls. We estimated that the 3-W and 4-W RVs accounted for approximately 50% and 10%, respectively, of the total OFP caused by diesel vehicles (including diesel trucks and RVs) in Beijing in 2012. Thus, more attention should be given to VOC emissions and their impact on ozone formation. Highlights: Thirteen RVs in Beijing were tested using PEMS. The VOC emissions of the tested RVs and their OFPs were analyzed. The RVs produced high proportions of aromatics and carbonyls. Attention should be given to the VOCs of RVs and their impact on ozone formation.